The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1088/1361-6587/aa6423
|View full text |Cite
|
Sign up to set email alerts
|

Ideal and resistive magnetohydrodynamic instabilities in cylindrical geometry with a sheared flow along the axis

Abstract: The problem of the linear stability of internal magnetohydrodynamic modes in a cylindrical plasma with a sheared longitudinal flow is addressed. A Newcomb-like equation describing the perturbation is derived and exactly solved for a class of analytic profiles for rotational transform, equilibrium flow and pressure. A dispersion relation for ideal modes is then derived and analysed for different limits of the poloidal mode number (viz. m = 1, > m 1 and  m 1). In the resistive case, a simple and exact expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…where n is the toroidal mode number, r s is the resonant point, s denotes the magnetic shear at r s and the parameter λ labels the profiles determining their steepness [18]. Note that we chose a reference frame which is moving along the longitudinal direction in a such way that the rotation frequency vanishes at r s (this is allowed within the cylindrical approximation).…”
Section: Equations For Resistive Magnetic Perturbationsmentioning
confidence: 99%
See 2 more Smart Citations
“…where n is the toroidal mode number, r s is the resonant point, s denotes the magnetic shear at r s and the parameter λ labels the profiles determining their steepness [18]. Note that we chose a reference frame which is moving along the longitudinal direction in a such way that the rotation frequency vanishes at r s (this is allowed within the cylindrical approximation).…”
Section: Equations For Resistive Magnetic Perturbationsmentioning
confidence: 99%
“…. It is found that the key parameter is the ratio y = Ω /ω A q /q of toroidal rotation shear and magnetic shear [18,19] The main task of a theoretical study of rf control of tearing instabilities, in the observable Rutherford phase, is the estimate of the necessary driven current, e.g. the rf power necessary to reduce the state variable w(t) and to design real-time strategies for the rf launching for an effective power deposition and possible tracking of the moving island.…”
Section: Equations For Resistive Magnetic Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.1017/S002237781800020X is approached. We expand (3.4) and (3.5) about r s giving (we use the same notation as in Mikhailovskii (1998), Brunetti, Lazzaro & Nowak (2017)):…”
mentioning
confidence: 99%
“…Also there are many studies proposing that plasma sheared rotation variously affects the stability properties of Tokamak equilibria in several cases, either inducing stabilization or destabilization (e.g. [5][6][7][8][9]), with the main destabilizing mechanism being the Kelvin-Helmholtz instability [10]. * dkaltsas@cc.uoi.gr † gthroum@uoi.gr ‡ morrison@physics.utexas.edu Furthermore, many astrophysical phenomena, such as the development of turbulence in various stages of the solar wind and in magnetized accretion disks, are consequences of flow-driven instabilities such as the Kelvin-Helmholtz instability (e.g.…”
Section: Introductionmentioning
confidence: 99%